Experimental Testing of Scroll Expander Performance for a 1 kW ORC Power Plant - Hinlailoed, Thanit; Koonsrisuk, Atit (RMUTP Research Journal Sciences and Technology, 2020)
The ORC power plant is a promising technology to generate electricity from low-temperature heat sources. However, implementation of the ORC for low capacity electricity generation is unattractive at the commercial level. Scroll compressors are massively produced to be used in refrigeration and air-conditioning applications. Using a scroll compressor in reverse, as an expander, can reduce the investment cost of low-capacity ORC power plants. In this study, 2 scroll compressors that are available in the automotive air-conditioning market of Thailand were modified and used as the expander of a 1 kW ORC power plant. The performances of these 2 scrolls were compared and the plant performance was investigated. A heat source temperature from 100°C to 150°C was supplied to the plant. It was found that the gross power is higher by 18-35% for the larger expander (110 cc/rev) than for the smaller expander (85.7 cc/rev). The larger one provides the isentropic efficiency of 37-76% and the gross power of 806-1,926 W. In addition, the effects of check valve installation were examined and compared with those of the tests without check valve installation. It was revealed that the isentropic efficiency increases by 18% while the gross power decreases by 4-22% when the check valve was installed.